Dermoscopy saga - A tale of 5 centuries - Jeta Buch; Sebastian Criton (Wolters Kluwer Medknow Publications, 2021)
The origin of dermoscopy can be traced back to the middle of the modern age and Borel's discovery (1655 - 1656) laid the foundation stone with important contributions from Ernst Karl Abbe, Unna, Muller, Saphier and others. However, the work done by Dr. Ronald Mackie (1971) for the early detection of melanoma marks the peak. The entire journey of evolution was eventful. This article is a brief overview on the history of dermoscopy and the contribution of various scientists leading to emergence of dermoscopy as an independent, dynamic field today.